Introduction of pneumococcal vaccine in national immunisation schedule in India: boon or bane? - Nayak, Ranjeeta; Kumar Singh, Arvind; Pragyan Parida, Swayam; Padhy, Sarmistha; Mishra, Kumar Guru (Public Health Review: International Journal of Public Health Research, 2019)
Vaccination is undoubtedly one of the most cost-effective child survival public health measure which are more affordable and accessible to community in preventing diseases. Government of India has undertaken several initiatives to strengthen maternal and child health services in the country and child immunisation being an important part of child healthcare system in India. The National Immunization Programme has taken many initiatives since its inception as Expanded Programme on Immunization in 1978. In recent years, there has been introduction of various newer vaccines. Introduction of pneumococcal vaccine in selected states in year 2017 and plan to scale up in the entire country is the newest change in National Immunization Schedule. This review aims to identify various articles related to pneumococcal infection and vaccine highlighting the burden, serotypic distribution, available vaccines, evidence regarding vaccine safety, efficacy, acceptability and cost effectiveness, in order to provide sufficient understanding on the demand and need of this vaccine in India. Important factors underpinned by this article are though there is a need of vaccination due to severe form of pneumococcal infections and antibiotic resistance due to which many developed countries have included PCV in their regular immunisation programmes, however studies regarding effectiveness of pneumococcal vaccines in developing countries like India, data regarding the burden of pneumococcal infections are not available. Also there are limited studies investigating the bacterial and viral etiology of Community Acquired Pneumonia and lack of data to show change in the serotype prevalence overtime. This review highlights the need of more research to provide substantial clinical and epidemiological evidence for the introduction of pneumococcal vaccine.